Analisis Marketing Mix Dalam Menimgkatkan Volume Penjualan Pada Ayam Geprek Kawasan Kampus Bukit Palembang - Saputra, Muhammad Arya; Saputra, Tedy Setiawan; Meilina, Echie; Ladyva, Jolinka Velichea (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This study aims to analyze the impact of marketing mix strategies on increasing sales volume for Ayam Geprek SMEs located in the Bukit Palembang campus area. Using a qualitative method with structured interviews with five SME owners and a literature review, the study found that elements of the marketing mix, including product, price, place, and promotion, significantly influence consumer attraction and sales volume growth. Product innovation, competitive pricing, strategic location, and social media promotion proved effective in attracting university students as the target market. The findings indicate that the implementation of an appropriate marketing mix strategy can provide a competitive advantage and boost the growth of Ayam Geprek in the area.